'Earrings and shields': metaphor and gendered discourses in female genital mutilation songs in Kuria, Kenya. (29th December 2016) - Wambura, Joyce
Abstract : Female genital mutilation (FGM) is a global issue affecting women and girls in different parts of the world. Over 140 million girls and women have undergone FGM worldwide. In the UK, 130, 000 girls and women live with the consequences of FGM (Reid 2014). In Kuria region of Kenya, 96% of women and girls have undergone FGM (Oloo et al 2010) despite its illegal status. FGM has been approached from the religious, medical and human rights perspectives but the linguistic perspective has not yet been considered. Drawing on Critical Discourse Analysis (CDA), this paper seeks to address the FGM issue from a linguistic perspective by analysing metaphors in female circumcision in Kuria Kenya. Focus is on how through discourse, gender inequalities are normalised and advanced within a sociocultural system and how this, in turn, contributes to legitimation of FGM. Findings show that metaphors function as discursive strategies for constructing and maintaining dominant patriarchal hegemonies and maintaining the status quo while reinforcing the perpetuation of FGM. I suggest that an understanding of the role of gender and discourse in FGM could influence efforts to end the practice and lead to positive change.